Improving quality of life in patients with end-stage age-related macular degeneration: focus on miniature ocular implants - Singer MA (Dove Medical Press, 2011)
Michael A Singer1, Nancy Amir2, Angela Herro3, Salman S Porbandarwalla3, Joseph Pollard11Medical Center Ophthalmology Associates, San Antonio, TX, USA; 2Santa Rosa Low Vision Clinic, San Antonio, TX, USA; 3University of Texas Health Science Center at San Antonio, San Antonio, TX, USAAbstract: Low vision devices in the past have been mainly extraocular. There are now four new devices in different stages of development and implementation that are currently available. Three of them, the Implantable Miniature Telescope (IMT, VisionCare Ophthalmic Technologies, Saratoga, CA), Intraocular Lens for Visually Impaired People (IOL-VIP, IOL-VIP System, Soleko, Pontecorvo, Italy), and Lipschitz Mirror Implant (LMI, Optolight Vision Technology, Herzlia, Israel) are implanted into the anterior segment while the Argus II (Second Sight Medical Products, Sylmar, CA) is implanted into the posterior segment. The goal of these devices is to increase the patient quality of life which has been measured by Visual Functioning Questionnaire (VFQ) scales. The IMT is the only device that has been shown to increase the VFQ score by seven points at 6 months compared to baseline. It is the only FDA-approved device in the US while the Argus has been approved in Europe. Each of these prosthetics has potential benefits for patients.Keywords: IMT, IOL-VIP, LMI, Argus II